Spatial Diversity in Composition and Structure of Nekton in Ngenep Spring and its Channels, Karangploso - Malang - Hapsari, Lia; Sihombing, Maic Audo Lin; Rohie, Ade Meylisa Crystel; Retnaningdyah, Catur (Graduate School, Universitas Brawijaya, 2014)
Water springs and its channel degradation due to anthropogenic pollution may alter the community structure of aquatic organisms. Water spring degradation therefore affect the quality of water as tourism resources. This study aims to investigate the changes in community structure of nekton and determine the relationships between water quality characteristics to the diversity of nekton. The field survey was set up in Ngenep spring and its channels. Results showed that nekton species found in Ngenep spring and its channels consists of 4 classes, 4 orders, 6 families, and 7 species with total 627 nekton samples. It is comprises of fishes, shrimp, frogs and waterstriders. Nekton diversity index (H') in the spring and irrigation channel were in moderate level (1<H'<3) while in settlement channel was low (0,67). Evenness values of nekton ranged 0,24 - 0,53, whereas dominancy index of nekton ranged 0,41 - 0,74. Evenness value in settlement channel was very low (0, 24) with high dominancy index (0, 74); it indicates that nekton species were spread not evenly in the channel, it dominated by fish Rasbora sp. (highest IVI, 184,95). There were spatial variations of physico-chemical water qualitiy parameters in Ngenep springs and its channels (temperature, stream velocity, turbidity, conductivity, pH, DO, BOD and TOM) which affected to nekton diversity and community structure. Clustering analyses and PCA result shows correlation pattern between nekton distribution with physico-chemical water quality parameters. However, physico-chemical water quality parameters in Ngenep springs and its channel were still optimum as nekton habitat (PP No. 82/ 2001). Keywords: Community structure, Nekton, Spatial diversity, Spring, Water channel